2021
DOI: 10.33549/physiolres.934773
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 and Klotho Are Associated With Trabecular Bone Score but Not Bone Mineral Density in the Early Stages of Chronic Kidney Disease: Results of the Cross-Sectional Study

Abstract: This study evaluates bone mineral density (BMD) and trabecular bone score (TBS) in relationship with new markers of chronic kidney disease (CKD), fibroblast growth factor 23 (FGF23), and klotho. The patients in this cross-sectional study were divided as follows: group A -patients in stages G1-3; group B -patients in stages G4 – 5 according to KDIGO. Plasma levels of soluble klotho and FGF23 were determined by ELISA. Bone mineral density (BMD) and trabecular bone score (TBS) were measured. 74 patients with CKD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Our research has reached a similar conclusion with Kužmová Z et al [25] and Baldan A et al [26] , that is, Klotho is a protein that protects bones. Klotho can reduce the incidence of OP, which means that it can promote the stability of bone trabecular structure and reduce the incidence of osteoporotic fractures.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our research has reached a similar conclusion with Kužmová Z et al [25] and Baldan A et al [26] , that is, Klotho is a protein that protects bones. Klotho can reduce the incidence of OP, which means that it can promote the stability of bone trabecular structure and reduce the incidence of osteoporotic fractures.…”
Section: Discussionsupporting
confidence: 91%
“…The variation of KL is related to the BMD of the population [22][23][24] . Kužmová Z et al [25] found that Klotho was positively correlated with trabecular bone score (TBS) in population with chronic kidney disease (CKD), and negatively correlated with fracture risk. Baldan A et al [26] also found that a decreased Klotho concentration is associate with a higher probability of having had fragility fractures in β-Thalassemia patients.…”
Section: Introductionmentioning
confidence: 99%
“…The association between Klotho and BMD requires further study. The available data are inconsistent; some studies show no relationship, 50 , 51 , 52 whereas others show a negative correlation. 53 Our findings in these 32 patients with CKD are worth reporting, but they do not allow us to make claims regarding pathogenetic relevance.…”
Section: Discussionmentioning
confidence: 95%
“…Recent clinical studies in CKD patients have found that lower levels of serum sKlotho are associated with bone impairment, particularly with altered trabecular microarchitecture [81]. Interestingly, the CARTaGENE health study showed that in CKD, both the lowest and the highest serum sKlotho levels were associated with fractures [82].…”
Section: Soluble Klotho As a Biomarker Of Cardiovascular And Bone Alt...mentioning
confidence: 99%